Classroom management in teaching-learning of english in large classes - Abd. Gani, Abdullah (Universiti Malaysia Sarawak, UNIMAS, 2003)
This research was conducted to find out the extent to which classroom management problems regularly faced by teachers are problems to the English as Second Language (ESL) teacher of the selected schools. In addition, this research also focuses on the effectiveness of the methods/strategies regularly used by teachers to the ESL teachers of these schools. The ESL teachers from SMK Semera and SMK Asajaya-Samarahan division were involved in this research.